Colombia : Arrangement Under the Flexible Credit Line and Cancellation of Current Arrangement- Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper focuses on recent economic developments as well as the role of the flexible credit line (FCL) arrangement. Despite a large external shock, Colombia's economy showed remarkable resilience in 2015. The current account deficit reached a record level in 2015, but reserves remained stable. The banking system and corporate sector remained in good financial health. Growth will be subdued in the near future but is projected to gradually return toward potential. The FCL has served Colombia well. The previous FCL arrangements have been instrumental to cope with heightened external risks in recent years, complementing the authorities' policy response to economic shocks.